Person-centred care as an evolving field of research: a scoping review - Forsgren, Emma; Feldthusen, Caroline; Wallström, Sara; Thunström, Lovisa; Kullman, Lars; Sawatzky, Richard; Öhlén, Joakim (Frontiers in Health Services, 2025)
IntroductionChanges in policy towards a healthcare approach viewing patients as persons provide calls for person-centred healthcare practices. The objective of this scoping review was to present an overview of the international literature on PCC.MethodsDatabase-specific search string including index terms and free text words related to PCC were constructed to identify relevant literature indexed in PubMed, Scopus, PsychINFO, CINAHL and Web of Science. Two different methods of combined manual and computer-assisted screening were applied to identify citations to be included in the review.ResultsIn total, 1,351 publications were included, whereof theoretical and empirical studies were most prevalent in the sample. For the latter, the most common setting was hospital care. The study population was most often health professionals or patients. The most frequently used term was patient-centred, followed by person-centred and family-centred. Research from six continents was included. An exploration of collaborations and research clusters has revealed several clusters.DiscussionThis review provides a snapshot of the literature on PCC. The lack of clarity in terminology presents barriers to comprehensively overviewing the vast amount of available research within the field, which in turn presents challenges for research-based policy and practice development.